Objective and automatic grading system of facial signs from smartphones' pictures in South African men: Validation versus dermatologists and characterization of changes with age. Issue 4 (27th April 2023) - Flament, Frederic; Jiang, Ruowei; Houghton, Jeff; Cassier, Matthieu; Amar, David; Delaunay, Caroline; Balooch, Guive; Bouhadana, Elisabeth; Aarabi, Parham; Passeron, Thierry
Abstract: Objective: To evaluate the capacity of the automatic detection system to accurately grade, from selfie pictures, the severity of eight facial signs in South African men. Methods: Selfie pictures (obtained from frontal and back cameras) of 281 South African men differently aged (20–70 years) were obtained and analyzed by an automatic artificial intelligence (AI)‐based automatic grading system. Data were compared with the clinical gradings made by experts and dermatologists. Results: In all facial signs, both series of gradings were found highly correlated with, however, different coefficients (0.59–0.95), those of marionette lines and cheek pores being of lower values. No differences were observed between data obtained by frontal and back cameras. With age, in most cases, gradings show up to the 50–59 year age‐class, linear‐like changes. When compared to men of other ancestries, South African men present lower wrinkles/texture, pigmentation, and ptosis/sagging scores till 50–59 years, albeit not much different in the cheek pores sign. The early onset (mean age) of visibility of wrinkles/texture for South African men were (i.e., reaching grade >1) 39 and 45 years for ptosis/sagging. Conclusion: This study completes and enlarges the previous works conducted on men of other ancestries by showing some South African specificities and slight differences with men of comparable phototypes (Afro American).